Fluxes of methane and distribution of sulfate as influenced by coastal salt-marsh soil ecosystem of Northern Germany - Khan, HR (Bangladesh Journal of Scientific and Industrial Research, 2017)
The study was conducted in Schleswig-Holstein at the Wadden sea coast of Northern Germany to evaluate the possible factors controlling methane (CH4) and sulfate (SO4) dynamics along a toposequence of daily to seasonally ?ooded coastal salt marsh soils. The soil at the top end of the salt marsh (with a height of 1.8 m above sea level: a.s.l. and a dense vegetation cover) was salic silty to clayic Typic Sulfaquent, while the soil at the bottom end (with some salt bushes and a 1.4 m a.s.l.) was sandy to silty Haplic Sulfaquent. The mean (depth: 0-100 cm) values of pH were around 7, and of redox potentials in the Typic Sulfaquent were ranged from -162 to +104 mV during all the seasons. The annual average emissions of CH4 were almost 10 fold higher (0.3 g m-2 a-1) in Haplic Sulfaquent than that (0.03 g m-2 a-1) of the Typic Sulfaquent. In all the pro?les, the concentrations of CH4 were very low and varied signi?cantly (p?0.05) with the seasons and soil depths. The concentrations of CH4 showed no dependence to temperature. The SO4 contents were observed maximum in the Typic Sulfaquent followed by Haplic Sulfaquent during all the seasons. There is no noticeable correlation was obtained between the SO4 and CH4 concentrations. Moreover, even CH4 was determined at depths where the SO4 concentration in the soil solution was around 1200 mg SO4 L-1. Bangladesh J. Sci. Ind. Res. 52(3), 177-186, 2017